MiRNA expression profile of mucoepidermoid carcinoma. (8th February 2018) - Binmadi, NO; Basile, JR; Perez, P; Gallo, A.; Tandon, M; Elias, W; Jang, SI; Alevizos, I
Abstract : Objectives: MicroRNAs (miRNAs) are single‐stranded RNAs that have been implicated in cancer initiation and progression and act as tumour suppressors or oncogenes. In this study, miRNA profiling was conducted on the most frequent malignancy of salivary glands, mucoepidermoid carcinoma (MEC), in comparison with normal tissues. Materials and Methods: The TaqMan Human miRNA Cards Array was used for the miRNA profiling of MEC and normal tissues. To validate the differentially expressed miRNAs in MEC, we used real‐time PCR (qRT‐PCR). Results: miR‐302a was the most significantly increased miRNA in cancer tissues ( p < .05). Here, we demonstrate that the upregulation of miR‐302a expression in SGT cell lines induced cancer cell invasion in vitro. Conclusions: These promising results suggest the need for further studies to establish mir‐302a as a marker of invasion and aggressiveness in MEC.